1991
DOI: 10.3109/00016359109005933
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin B status and response to replacement therapy in patients with burning mouth syndrome

Abstract: The aim of the study was to determine, in a group of patients with therapy-resistant burning mouth syndrome (BMS), the possible deficiency of vitamins B1, B2, and B6 and the effect of proper vitamin replacement therapy. Sixteen individuals, aged 47 to 81 years, participated in the study. All underwent a base-line examination comprising anamnestic information, subjective assessment of symptoms, dietary registration, salivary analysis, and serum analysis of thiamine (B1), riboflavine (B2), and pyridoxine (B6). F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0
6

Year Published

2000
2000
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(38 citation statements)
references
References 15 publications
0
32
0
6
Order By: Relevance
“…[2][3][4][5] We also previously reported psychiatric aspects of patients with BMS, including an assessment of the patients' personalities, 6,7 and an investigation into the presence of neurotic characteristics using the Rorschach method. 8 Hormonal disturbances associated the menopause [9][10][11] and vitamin deficiencies 12,13 are possible causal factors. However, the etiology and neurophysiological mechanisms of the BMS are still unknown.…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4][5] We also previously reported psychiatric aspects of patients with BMS, including an assessment of the patients' personalities, 6,7 and an investigation into the presence of neurotic characteristics using the Rorschach method. 8 Hormonal disturbances associated the menopause [9][10][11] and vitamin deficiencies 12,13 are possible causal factors. However, the etiology and neurophysiological mechanisms of the BMS are still unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Reports looking at the role of vitB6 are in fact limited to two studies [9] and [10], and some anecdotal reports [11]. Interestingly, these two studies showed contradictory results.…”
Section: Discussionmentioning
confidence: 99%
“…However, a proper control for assessment of a placebo effect was missing in their investigation. The study carried out by Hugoson A. et al [10] was intended to control this flaw and used a placebo control to explore possible involvement of vitamin B1, B2 and B6 deficiency in the development of BMS. Besides the absence of efficacy of proper vitamin replacement therapy in patients suffering a vitB1 and B2 deficiency, no vitB6 deficiency was found in their samples.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Além disso, alguns estudos sugerem que a SAB está associada a baixos níveis séricos de ferro e zinco (Lamey et al, 1996;Thorstensson, 1991 (Scala et al, 2003).…”
Section: Associação De Fatores Clínicos Na Sabunclassified